Intraoperative and postoperative physiological monitoring practices by pediatric dentists - Aka, W; Jedrychowski, J R (The Journal of clinical pediatric dentistry, 1995)
The medical and dental literature has described successful sedations and those which have resulted in injury and death. Physiologic monitoring of patients is essential in assuring the success and safety of sedations in the dental office. The purpose of this study was to investigate the utilization and preferences of various physiologic monitoring methods and utilization of dentist anesthesiologists by pediatric dentists during sedations. Pediatric dentists in California were surveyed [n = 261] regarding monitoring methods in five different case scenarios. The most frequently utilized methods were clinical observation, pulse oximeter, and precordial stethoscope. Eighty seven percent of the pediatric dentists who use sedation do so without the involvement of a dentist anesthesiologist. Eighteen percent of pediatric dentists do not use any sedative agents in their practice. In the five case scenarios described in the survey, clinical observation was the most frequently utilized monitoring method during intra- and postoperative periods, followed by the pulse oximeter and precordial stethoscope. Intra- and postoperative monitoring varied with the complexity of the case scenario and most respondents monitored continuously. The trends observed from this study indicate that recent graduates use more sedative agents and find the pulse oximeter to be useful for physiologic monitoring during sedation.